STUDY ON THE CONTENT FORMALINFRESH (Restrelliger Sp) CONTAINEDMARKET OF PEKANBARU CITY - Wardhana, Akbar; Mus, Sukirno; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aimed to evaluate the safety quality fresh Restrelliger Spsold in the market around of Pekanbaru. Fresh Restrelliger Sp obtained from 5 traditional markets and 3 modern market in the city. A total of 24 samples were analyzed on the content of Formalin, Coliformbacteria, and Vibrio Spbacteria. pH condition. The results of the study concluded that there was no evidence of illegal ussing food additives ( formalin ) in all of the market around of Pekanbaru. No Coliform bacteria and Vibrio parahaemolitycus on fresh Restrelliger Sp. whereas the V. cholerae bacteria found in one sample. In one of the market. The results of the analysis of pH show that the range of pH amount 5.67 to 6.15.Keywords: Restrelliger Sp, Fish Quality, Formalin